Impact Analysis of Land Use on Time Lag and Peak Discharge in the Downstream Area of Sadia Watershed Bima City West Nusa Tenggara using HEC-HMS and SCS-CN - Hartawan, I Putu; Siddik, Firmana; Firmana, Ary; Susetyo, Ekanto Wahyudi; Harlan, Dhemi; Handyastono, Bagus; AS Algoul, Mohammed (TEKNIK, 2025)
Flood events have frequently occurred in the downstream area of the Sadia Watershed (DAS) in Bima City, West Nusa Tenggara. In recent years, the overflow of the Sadia River has been triggered by land use changes and the impacts of climate change. This study aims to analyze land cover changes in 2015, 2019, and 2022, and to evaluate their impact on flood peak discharge using hydrological simulations, land cover data were analyzed using ArcGis software and integrated with hydrological modeling using HEC-HMS. The Synthetic Unit Hydrograph (HSS) SCS-CN method was used in the simulation with a 25-year return period, following calibration of the Sadia River’s bank full discharge to ensure model accuracy. The simulation results showed an increase in the peak discharge entering the Sadia River, from 156,20 m³/s in 2015 to 164,80 m³/s in 2019, and 167,00 m³/s in 2022. Additionally, the time lag decreased from 445.15 minutes in 2015 to 431.84 minutes in 2019 and 429.88 minutes in 2022. The increase in the Curve Number (CN) value and impermeable area indicates a reduction in soil infiltration capacity due to land conversion. However, climate factors, such as increased rainfall intensity, also contributed to the rise in peak discharge. These findings can serve as a basis for better land use management and emphasize the importance of considering climate factors when designing flood risk mitigation efforts, especially in the face of increasing flood events.